Construct of reality: through the photo realistic works of Richard Estes - Brnic, Tanja (My University, 2019)
In this research I explore aspects of the work of the Photorealist painter Richard Estes as a lens through which I examine aspects of my own practice as a painter. Estes works from a multitude of photographs of everyday urban scenes as a fragmented “mirror” of a visual or perceptual reality in a way which parallels my own practice. As an artist, in my own practice, I am challenged constantly with transforming the external three dimensional visual world on to the two dimensional surface of the canvas. I paint from photographs as a means of capturing a specific moment in time and place. The process allows for reflection of my own reality, my everyday experiences and thoughts. This study does not claim to make an original contribution to our understanding of Realism or Photorealism, so much as to synthesise some key ideas and perceptions and apply these to the understanding of my own processes as a painter working in this mode. I will focus on the concept of “the construction of reality” as the interplay between what is “real” and what is perceived through photorealistic paintings of reflections and distortions. Painting, in my and Estes’ practice, is a means of transforming a temporary moment into something more permanent. Through a close analysis of a selection of Estes’ realistic paintings of everyday scenes of New York City which he manipulates, visually changing the original, I am able to discuss and contextualise my own painterly processes. I then extend this case study focus to a wider consideration of a number of art historical and theoretical perspectives on Realism and Photorealism. The aim is to engage in a dialogue with my series of work, discussed more fully in the final chapter, that represent in two dimensions, my own construct of an experienced three dimensional reality.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Arts in Fine Arts to the Faculty of Humanities, Wits School of Arts, University of the Witwatersrand, Johannesburg, 2019
Keywords: Art, Modern-20th century; Artists-South Africa